Reimagining a Lost Armenian Home: The Dildilian Photography Collection - Marsoobian, Armen (I.B. Tauris, 2017)
For nearly a century members of the Dildilian family practiced the art of photography in Ottoman Turkey, Greece and the United States. This book contains over 200 photographs, primarily from the Ottoman era, beginning with the creation of the family business by Tsolag Dildilian in Sivas in central Turkey in 1882 and concluding in 1922 in Samsun, when the family was forced into exile in Greece. The photographs and the stories that unfold around them capture a defining period in the nearly three thousand year history of the Armenians in Anatolia and the Armenian Highlands. The early-twentieth century witnessed the violent erasure of the Armenians from their historic homeland, with catastrophic effects for the Dildilian family and their community. Yet this was also a period of unprecedented educational, cultural and commercial development for the Armenians. The Dildilian family was intimately involved in the triumphs and tragedies of these years and this book, through its rich pictorial history, sheds unprecedented light on the real-life experiences of Armenians in the devastating years of the Armenian Genocide and beyond. It is an unusual and original contribution to the social history of the Near East.
Keywords: Dildilian family; Armenians; Pictorial works; Portraits; Armenia; dept.phi; faculty_collection

Fragments of a Lost Homeland: Remembering Armenia - Marsoobian, Armen (I.B. Tauris & Co. Ltd., 2015)
SCSU Faculty Scholar Award
Keywords: 1801-1900; Dildilian family; Armenian Genocide; 1915-1923; History; Personal narratives; Armenian; Armenian Genocide; 1915-1923; Armenia; SCSU Faculty Scholar Award; award_winner; dept.phi; faculty_collection

The making of modern Turkey: nation and state in eastern Anatolia, 1913–1950 - Marsoobian, Armen T (Journal of Genocide Research, 2013)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/123-399-132-760-077 tex.type: [object Object]
Keywords: dept.phi

The eclipse and rebirth of american philosophical pluralism: a history lesson about his-tory - Marsoobian, Armen T (Wisdom, 2016)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/136-369-053-718-764
Keywords: dept.phi

Acknowledging intergenerational moral responsibility in the aftermath of genocide - Marsoobian, Armen T (Genocide Studies and Prevention, 2009)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-944-111-369-330 tex.type: [object Object]
Keywords: dept.phi

Breaking the silence: Memorialization and cultural repair in the aftermath of the armenian genocide - Marsoobian, Armen T. (Mass Violence and Memory in the Digital Age, 2020)
Keywords: dept.phi

Genocide by other means: heritage destruction, national narratives, and the Azeri assault on the indigenous Armenians of Karabakh - Marsoobian, Armen T. (Genocide Studies International, 2023)
The propaganda efforts of the authoritarian Aliyev regime in Baku and the general Western ignorance of the history of the South Caucasus have contributed to the lack of meaningful response to the genocidal aggression that Azerbaijan has inflicted on the indigenous Armenians of Artsakh, known to many as Nagorno-Karabakh. The humanitarian crisis created by the Azeri blockade of the Lachin Corridor is only the most recent step in a process of cleansing the region of its Armenian population, a process that began in the early years of the twentieth century. The Ottoman Turkish genocide of Armenians in 1915–1923 is not a distinct event of the past but a process whose ideology is central to the Azeri-Turkish genocidal violence perpetrated against Armenians in the present. An integral component of the processes of genocide is cultural heritage destruction as noted by Raphael Lemkin. The erasure of most signs of the indigenous Armenian presence on its historic homeland was particularly pronounced in the decades following the Armenian Genocide and continues today. Cultural erasure went hand in hand with Turkish state genocide denial and the rewriting and mythologizing of its national narrative. Azerbaijan has been following a similar playbook since the collapse of the Soviet Union. These genocidal processes of denial, heritage destruction, and the rewriting of history are what I describe as “genocide by other means.”
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi; genocide; heritage destruction; national narratives; peer-reviewed; violence

How do we memorialize genocide? The case of the German memorial to the murdered Jews of Europe - Marsoobian, Armen T (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This book explores the memory and representation of genocide as they affect individuals, communities and families, and artistic representations. It brings together a variety of disciplines from public health to philosophy, anthropology to architecture, offering readers interdisciplinary and international insights into one of the most important challenges in the 21st century. The book begins by describing the definitions and concepts of genocide from historical and philosophical perspectives. Next, it reviews memories of genocide in bodies and in societies as well as genocide in memory through lives, mental health and transgenerational effects. The book also examines the ways genocide has affected artistic works. From poetry to film, photography to theatre, it explores a range of artistic approaches to help demonstrate the heterogeneity of representations. This book provides a comprehensive and wide-ranging assessment of the many ways genocide has been remembered and represented. It presents an ideal foundation for understanding genocide and possibly preventing it from occurring again
tex.ids: lens.org/001-902-062-832-38X, marsoobianHowWeMemorialize2018
Keywords: Aesthetics; Counter-monument; Health Psychology; Health psychology; History of World War II and the Holocaust; Holocaust; James E. Young; Jochen Gerz; John Dewey; Marian Marzynski; Memorial to the Murdered Jews of Europe; Memorial to the murdered jews of europe; Modernism; Noël Carroll; Peter Eisenman; Public Health; Public health; Public memorials; Sociology; Sociology; general; World War; 1939-1945; dept.phi

Collective memory, memorialization and bearing witness in the aftermath of the Armenian Genocide - Marsoobian, Armen T. (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter describes and analyzes an ongoing project of memorialization of the Armenian Genocide in Turkey. It explores the importance of memorialization for collective historical memory, especially in situations where historical memory has been subverted by genocide denial. Among many aspects of memorialization, its role in bearing witness is explored and highlighted. Three components of the memory project are described: (1) the photography exhibitions, (2) the publications, and (3) the creation of memory sites. The project centers on the story of the Dildilian family in Ottoman Turkey before, during, and after the genocide, covering the years 1872–1923. A microhistory of the life of the Armenian minority is chronicled by means of the personal memories and stories of members of the family. The history is richly illustrated with photographs and drawings that serve as the basis of the photography exhibitions and books. Exhibitions and associated talks and panels have taken place in Istanbul, Merzifon, Diyarbakir, and Ankara. The chapter describes and analyzes the reaction of the Turkish public to the project.
Citation Key Alias: lens.org/145-690-138-443-429
Keywords: Armenian Genocide; Bearing witness; Collective memory; Genocide denial; Memorialization; Turkey; dept.phi

The Blackwell Guide to American Philosophy - Marsoobian, Armen; Ryder, John (Blackwell Pub., 2004)
Keywords: Philosophy; American; dept.phi; faculty_collection

Genocide's Aftermath: Responsibility and Repair - Card, Claudia; Marsoobian, Armen (Blackwell Pub., 2007)
Keywords: Genocide; Government policy; Genocide; History; Genocide; Moral and ethical aspects; Genocide; Prevention; dept.phi; faculty_collection

Introduction: genocide's aftermath - Card, Claudia; Marsoobian, Armen T (Metaphilosophy, 2006)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/017-589-143-645-589 tex.type: [object Object]
Keywords: dept.phi

The power of personal archives in witnessing, teaching, and visual storytelling: the Armenian memory project - Masud, Catherine; Marsoobian, Armen T (Journal of Human Rights Practice, 2024)
Abstract The Armenian Memory Project (AMP) is a collaborative effort designed to harness the energy and resources of the University of Connecticut and the New England Armenian community for the goal of fostering greater understanding of the region’s Armenian cultural heritage and the impact human rights crimes had on the Armenian community. In 2019, students and faculty from the university worked with Armenian American institutions and individuals on an initial component of the AMP, employing digital media technology to tell the story of one immigrant Armenian family, the Dildilians. A unique course was created to produce a documentary film centring around this family’s experiences in Ottoman Turkey before, during, and after the Armenian Genocide. Designed and taught by a documentary filmmaker with support from a family archivist/historian, the course brought students together in a collaborative learning experience. By immersing themselves in the family’s extensive photograph archive, these students came to understand the important role that the past continues to play in the lives of present-day Armenians. Furthermore, by taking on the responsibility as storytellers of the Dildilian narrative, students developed a deeper identification with this distant history and, in a wider sense, an appreciation for the ethical value of memory in bearing witness to the past. This collaborative and participatory framework for teaching using archival collections can serve as a model for creating a transformative learning experience in the study of human rights, war, and genocide.
Keywords: dept.phi; peer-reviewed

Criticism and compassion: the ethics and politics of Claudia Card - Dillon, Robin S.; Marsoobian, Armen T. (Wiley, 2018)
Criticism and Compassion: The Ethics and Politics of Claudia Card offers a unique perspective on the range of issues explored by Card during her distinguished career in philosophy. Investigates her work as an early leader in the development of feminist philosophy, challenging many preconceptions about the society’s norms regarding gender, marriage, and motherhood Crossing many disciplinary boundaries, her concept of social death has come to play a significant role in multidisciplinary field of genocide studies This volume combines many of Claudia Card’s important essays with recently commissioned essays by leading philosophers whose work has been influenced by Card The full scope of Card’s philosophy is presented here - both in her own words and those of her critics and interpreters
Keywords: dept.phi

The Philosophical Challenge of September 11 - Rockmore, Tom; Margolis, Joseph; Marsoobian, Armen (Blackwell Pub., 2005)
Keywords: Philosophy; Philosophy; Political science; September 11 Terrorist Attacks; 2001; Terrorism; United States; Terrorism; dept.phi; faculty_collection

The suppression of cultural memory and identity in Bosnia and Herzegovina - Pettigrew, David (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter identifies an orchestrated effort in “Republika Srpska”—an entity within Bosnia and Herzegovina that was recognized by the 1995 Dayton Peace Agreement − that is designed to prevent survivors of the genocide from erecting memorials to the victims in such locations as Višegrad, Prijedor, and Foča. While memorials for victims have been prohibited, and survivors have been prevented from using the term “genocide,” memorials to the perpetrators have been installed in the center of Višegrad, and near the Trnopolje concentration camp in Prijedor Municipality. In the hills above Sarajevo, in a location from which the city’s residents were attacked during the siege, a plaque honoring indicted war criminal Ratko Mladić has been installed. Accordingly, this chapter considers the extent to which the discriminatory practices regarding memorials in Republika Srpska constitute a violation of human rights. Further, the chapter argues that, following Raphael Lemkin’s definition of genocide, the prohibitive policies in Republika Srpska with respect to memorials and commemorative practices constitute nothing less than a continuation of the genocide, a second phase of the genocide designed to ensure the permanent erasure of a world that was destroyed. These human rights violations and the continuation of the genocide are a troubling testament to the failure of the international community in Bosnia, and to the problematic legacy of the Dayton Peace Agreement.
tex.ids: lens.org/044-520-161-353-25X, pettigrewSuppressionCulturalMemory2018a
Keywords: Apartheid; Cultural memory; Dayton Peace Agreement; Dayton peace agreement; Health Psychology; Health psychology; History of World War II and the Holocaust; Human rights; Prohibited memorials; Public Health; Public health; Raphael Lemkin; Sociology; Sociology; general; World War; 1939-1945; dept.phi

The Armenian genocide in film: overcoming denial and loss - Marsoobian, Armen T (The history of genocide in cinema: atrocities on screen, 2017)
Keywords: dept.phi